A inclusão como dispositivo econômico para o governo das pessoas com deficiência - PEREIRA, Sara Bianca da Silva (2019)
The present work deals with the inclusion and the government of people with disabilities, from a look in the Foucaultian studies. The elaboration of this work had as a research problem: how the inclusion of people with disabilities in the labor market has been constituted in a governmentality strategy? As a general objective, we define investigate how inclusion has been constituted in a strategy of governmentality in the economic field. In approaching the concept of governmentality with that of inclusion, we base our research on the analyzes produced by the theorist Michel Foucault. As a theoretical reference to subsidize the research, the main authors used were: Gallo (2015), Lopes (2009), Rech (2013), Sardagna (2013), Santaiana (2013) among other authors who discuss the use of governmentality in the process inclusion of people with disabilities. To that end, we raised some questions to subsidize the research problem, about actions that legitimized the inclusion process, based on the assumption that the Declaration of Salamanca designates that the school is responsible for the student's transition to the job market? What is the contribution of the Quotas Law to the insertion of people with disabilities in the labor market? What is the intention of the UN in producing speeches of equality of rights between people? The focus given to these questions was aimed at discussing legal and theoretical assumptions, thus providing a better understanding of the economic issues that currently have curtailed the inclusion process, and that naively is not perceived. The reference work was built through documentary research and discourse analysis, under the Foucaultian perspective. This type of research made it possible to establish a more critical and questioning view of the present, contributing to the problematization of the current social practices. Based on the studies and reflections experienced during the construction of this research, we conclude that through the discourses and practices that seek to promote inclusion, the subjectivation, the life of the population to be included, is conducted in a way that can be modified according to the mold of a capitalist society, where everyone needs to be included in economic games. The relevance of this research, in so far as it allows for the amplification of the theoretical-scientific researches. contributing to new knowledge about the inclusion of people with disabilities.